2021
DOI: 10.3390/buildings11060238
|View full text |Cite
|
Sign up to set email alerts
|

Kriging Metamodel-Based Seismic Fragility Analysis of Single-Bent Reinforced Concrete Highway Bridges

Abstract: Uncertainty quantification is an important issue in the seismic fragility analysis of bridge type structures. However, the influence of different sources of uncertainty on the seismic fragility of the system is commonly overlooked due to the costly re-evaluation of numerical model simulations. This paper aims to present a framework for the seismic fragility analysis of reinforced concrete highway bridges, where a data-driven metamodel is developed to approximate the structural response to structural and ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…GPR analysis is a type of regression analysis that is adopted when the dependent variable follows the Gaussian process [20,25,26]. Phan et al [27] and Hoang et al [28] used the GPR technique for seismic vulnerability and seismic fragility analysis for storage tanks and reinforced concrete highway bridges. Jung et al [20] also investigated several methods in estimating the maximum displacement and found that the GPR approach showed the best performance.…”
Section: Estimation Model Based On Gaussian Process Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR analysis is a type of regression analysis that is adopted when the dependent variable follows the Gaussian process [20,25,26]. Phan et al [27] and Hoang et al [28] used the GPR technique for seismic vulnerability and seismic fragility analysis for storage tanks and reinforced concrete highway bridges. Jung et al [20] also investigated several methods in estimating the maximum displacement and found that the GPR approach showed the best performance.…”
Section: Estimation Model Based On Gaussian Process Regressionmentioning
confidence: 99%
“…The levels for IO, LS, and CP determine the acceptance range of MIDR using the maximum height. The performance levels have threshold values considering the IO (0.7%), LS (2.5%), and CP (5.0%) to provide the MIDR limits [27,28,45,46]. Generally, the structural analysis that produces the fragility curve is conducted based on the PGA of 0.0 g in the fragility function.…”
Section: Six-floor Building Analysis For Development Of the Rapid Prediction Modelmentioning
confidence: 99%
“…The ensemble of decision trees (EDT) is a regression model capable of dealing with large amounts of data [23]. The Kriging model, which is an interpolation model, passes exactly through the experimental points and can form complex models with a limited amount of data [16]. It is also possible to analyze prediction uncertainty using this model [26].…”
Section: Metamodelingmentioning
confidence: 99%
“…In the former method, the accuracy of the metamodel significantly affects the optimal design results. In most extant studies, the experiments were conducted to approximate the relationship between the input and output variables using only one metamodel technique [15,16]. However, due to the existence of a variety of metamodeling techniques, it is important to apply the most appropriate one for each design problem.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the impact of the mixer is significant, and the use of a dual-mixer results in a remarkable increase in the urea conversion rate and NH 3 uniformity index by 169.5% and 136.4%, respectively. The techniques mentioned above are optimized using methods of trial-and-error and the design of experiment (DOE) [11,12]. These methods can help in easily planning experiments; however, it is difficult to represent the performance across the entire range of the design.…”
Section: Introductionmentioning
confidence: 99%